The protease of herpes simplex virus type 1 is essential for functional capsid formation and viral growth. - Gao, M (1994)
The herpes simplex virus type 1 protease and related proteins are involved in the assembly of viral capsids. The protease encoded by the UL26 gene can process itself and its substrate ICP35, encoded by the UL26.5 gene. To better understand the functions of the protease in infected cells, we have isolated a complementing cell line (BMS-MG22) and constructed and characterized a null UL26 mutant virus, m100. The mutant virus failed to grow on Vero cells and required a complementing cell line for its propagation, confirming that the UL26 gene product is essential for viral growth. Phenotypic analysis of m100 shows that (i) normal amounts of the c and d forms of ICP35 were produced, but they failed to be processed to the cleaved forms, e and f; (ii) viral DNA replication of the mutant proceeded at near wild-type levels, but DNA was not processed to unit length or encapsidated; (iii) capsid structures were observed in thin sections of m100-infected Vero cells by electron microscopy, but assembly of VP5 into hexons of the capsid structure was conformationally altered; and (iv) nuclear localizations of the protease and ICP35 are independent of each other, and the function(s) of Na, at least in part, is to direct the catalytic domain N(o) to the nucleus.